Decision-making nei Pazienti sottoposti a Trattamento Dialitico una ipotesi di ricerca sul Disjunction Effect - Silvia Dell'Orco, Martina Messina, Anna Di Leva, Giuseppina di Ronza, Marco Letterese, Tommaso Romitelli, Margherita Rosato, Barbara Vitulano, Vania Costa (Marp Edizioni, 2020)
Introduction: Before becoming an object of cognitive science, the topic of decision-making has questioned thinkers from all ages and disciplines: philosophers, mathematicians, logicians, economists and more. More recent studies have highlighted the neuroscientific basis of decision-making and the complex cognitive strategies involved in economic and social decisions, such as gambling. Aims: This paper aims to focus attention on the role of stress in influencing individuals' decision-making skills, especially in situations of risk and uncertainty. In particular, if on the one hand it is intended to investigate the relationship between stress and decisions of dialysis patients, on the other hand it is intended to highlight the so-called disjunction effect according to which decision-making situations with an uncertain outcome may lead to violate the axioms of neoclassical rationality. Method: Starting from an analysis of the literature on decision making, attention will be focused on stress factors that influence the decision making behaviour and cognitive strategies of the dialysis-treated patients. Conclusion: The review highlights the need to further investigate the disjunction effect and opens the way to the possibility of conducting experimental research to verify the presence of this effect in the specific case of these patients.